MERAWAT KEBERAGAMAN MENJAGA TOLERANSI MENEROPONG PERAN FORUM KERUKUNAN UMAT BERAGAMA KABUPATEN SIKKA - M. Harudin; Khaidir Khaidir; H. Rodja Abdul Natsir (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The government has the duty and obligation to protect every citizen from embracing their respective religions and providing teaching guidance that can be carried out safely and in an orderly manner, based on applicable laws. This study aims to determine the role of religious harmony forums in maintaining tolerance between religious communities in the Sikka Regency. This research uses a qualitative approach data collection using observation techniques, interviews, and study documentation. The informants in the interview are religious leaders. The results obtained are: FKUB has carried out various activities following the duties and functions of other mediators and motivators, FKUB conducted socialization, values in each religion, held dialogues with religious leaders and community leaders, accommodated and channeled the aspirations of religious organizations and goals society but is constrained by operational cost factors.